Unphysiological lung strain promotes ventilation-induced lung injury via activation of the PECAM-1/Src/STAT3 signaling pathway - Liu, Gang; Dong, Bin-Bin; Ding, Zi-Heng; Lan, Chao; Zhu, Chang-Ju; Liu, Qi (Frontiers in Pharmacology, 2025)
IntroductionIn patients with acute respiratory distress syndrome, mechanical ventilation often leads to ventilation-induced lung injury (VILI), which is attributed to unphysiological lung strain (UPLS) in respiratory dynamics. Platelet endothelial cell adhesion molecule-1 (PECAM-1), a transmembrane receptor, senses mechanical signals. The Src/STAT3 pathway plays a crucial role in the mechanotransduction network, concurrently triggering pyroptosis related inflammatory responses. We hypothesized that the mechanical stretch caused by UPLS can be sensed by PECAM-1 in the lungs, leading to VILI via the Src/STAT3 and pyroptosis pathway.MethodsA VILI model was established in rats through UPLS. The link between lung strain and VILI as well as the change in the activation of PECAM-1, Src/STAT3, and pyroptosis was firstly being explored. Then, the inhibitors of PECAM-1, Src, STAT3 were adopted respectively, the effect on VILI, inflammation, the Src/STAT3 pathway, and pyroptosis was evaluated. In vitro, human umbilical vein endothelial cells (HUVECs) were used to validate the findings in vivo.ResultsUPLS activated PECAM-1, Src/STAT3 signaling pathway, inflammation, and pyroptosis in the VILI model with rats, whereas inhibition of PECAM-1 or the Src/STAT3 signaling pathway decreased lung injury, inflammatory responses, and pyroptosis. Inhibition of PECAM-1 also reduced activation of the Src/STAT3 signaling pathway. The mechanism was validated with HUVECs exposed to overload mechanical cyclic stretch.ConclusionsThis study suggests that UPLS contributes to VILI by activating the PECAM-1/Src/STAT3 pathway and inducing inflammatory responses as well aspyroptosis.